Effects of road transportation on excitability scores of pigs administered with ascorbic acid during the hot-dry season - Olayinka Oluwafemi Asala; Joseph Olusegun Ayo; Adeshina Yahaya Adenkola; Ndazo Salka Minka (African Journal of Pig Farming, 2016)
This study was carried out in order to determine the effect of eight-hour road transportation on the excitability scores of pigs administered ascorbic acid (AA) during the hot-dry season in Northern Nigeria. Thirteen experimental pigs were administered with AA orally at 100 mg/kg, while ten control pigs were given only distilled water orally. Excitability score of each pig was determined 30 min before and immediately after transportation by a single ‘blind’ observer during weighing. An excitability score of 4 indicated the highest excitability. Percent excitability of experimental and control pigs with each score was also determined. Post-transportation, an increase in the percentage of experimental pigs with excitability score of 4 was recorded (38.5 to 69.2%), while a decrease was obtained in the control pigs (40.0 to 10%). Road transportation decreased the excitability scores and percent excitability in control pigs with high scores. In conclusion, administration of AA increased the nervous excitability of pigs transported by road during the hot-dry season in northern Nigeria.